Role of D-galactose-induced brain aging and its potential used for therapeutic interventions - Shwe, Thazin; Pratchayasakul, Wasana; Chattipakorn, Nipon; Chattipakorn, Siriporn C. (Experimental gerontology, 2018)
Aging is a phenomenon that all living organisms inevitably face. Every year, 9.9million people, globally, suffer from dementia, an indicator of the aging brain. Brain aging is significantly associated with mitochondrial dysfunction. This is characterized by a decrease in the activity of respiratory chain enzymes and ATP production, and increased free radical generation, mitochondrial deoxyribonucleic acid (DNA) mutations, and impaired mitochondrial structures. To get a better understanding of aging and to prevent its effects on many organs, chronic systemic administration of D-galactose was used to artificially create brain senescence in animal models and established to be beneficial for studies of anti-aging therapeutic interventions. Several studies have shown that D-galactose-induced brain aging which does so not only by causing mitochondrial dysfunction, but also by increasing oxidative stress, inflammation, and apoptosis, as well as lowering brain-derived neurotrophic factors. All of these defects finally lead to cognitive decline. Various therapeutic approaches which act on mitochondria and cognition were evaluated to assess their effectiveness in the battle to reverse brain aging. The aim of this article is to comprehensively summarize and discuss the underlying mechanisms involved in D-galactose-induced brain aging, particularly as regards alterations in brain mitochondria and cognitive function. In addition, the aim is to summarize the different therapeutic approaches which have been utilized to address D-galactose-induced brain aging. •D-galactose is the artificial senescence drug to induce aging process.•D-galactose induces brain aging via mitochondrial dysfunction.•Various interventions could reverse D-galactose induced brain aging.